AB1074 Understanding infusion reactions and their relationship to urate lowering in patients with refractory chronic gout (RCG): Pooled data from pegloticase trials. (23rd January 2014) - Baraf, H.; Yood, R.; Sundy, J.; Ottery, F.; Becker, M.
Abstract : Background: Pegloticase is a pegylated, mammalian recombinant uricase approved in 2010 in the US for the treatment of chronic gout refractory to conventional therapy. Objectives: Gout flares and infusion-related reactions (IRs) were the most commonly reported adverse events (AEs) in recently published Phase 3 pegloticase trials. 1 Post-hoc analyses of IRs following these trials revealed a relationship between these events and serum urate (SUA) levels. Here we provide details of the IR data, with the aim of maximizing the safety of pegloticase administration by reducing IR risk. Methods: 212 patients (pts) with RCG were treated with pegloticase 8 mg (biweekly or monthly) or placebo in 2 replicate 6-month blinded, randomized controlled trials (RCTs) and one open-label extension (OLE) study (N=151 enrolled; n=149 treated). A total of 5887 pegloticase infusions were administered. IR was defined as an adverse event (AE) occurring during or within 2 hrs of infusion. Safety was assessed by AE reports and lab tests. Per protocol pts were to receive IR prophylaxis (fexofenadine 60 mg the night before and the morning of each infusion; paracetamol 1000 mg and hydrocortisone 200 mg IV prior to each infusion). Results: IRs were reported overall in 26% (22/85 biweekly) and 42% (35/84 monthly) of pegloticase-treated pts in the RCTs and in 44% (65/149) of pts in the OLE study. Discontinuations from study or study drug owing to IRs occurred in 11% (9/85 pegloticase biweekly) and 13% (11/84 pegloticase monthly) of pts in the RCTs and in 11% (16/149) of pts in the open-label extension. Among the 16 pts in the OLE who discontinuted treatment, 2 were responders, 7 were non-responders and 7 had been treated with placebo in the RCTs (thus were not classified by RCT responder status). For all 3 studies, pts with SUA <6 mg/dL on the day of infusion had fewer than 1 IR per 100 infusions. 91% of IRs in the randomized trials and 88% of IRs in the extension study occurred when SUA exceeded 6 mg/dL on the day of infusion. The most common signs and symptoms associated with IRs were chest pain, back pain, flushing, muscle spasms, erythema/hyperemia, nausea/vomiting, abdominal discomfort, dyspnea, hyperhidrosis, headache, blood pressure increase or decrease, urticaria and pruritis. Among individuals with a first exposure to pegloticase during the RCTs or OLE study (n=208), 12 pts experienced IRs (reviewed retrospectively) with signs and symptoms consistent with a published definition of anaphylaxis. 2 All IRs resolved with supportive measures and no patients required intubation, mechanical ventilatory support, pressors, or hospitalization. No deaths were associated with IRs in the RCTs or OLE. Conclusions: All IRs observed in these clinical studies resolved with conservative medical management. Routine pre-infusion measurement of serum urate and discontinuation of pegloticase in pts showing loss of urate-lowering efficacy would have avoided approximately 90% of infusion-related reactions in these trials. References: Sundy et al. JAMA 2011;306:711-720. Sampson et al. Ann Emerg Med 2006;47:373-380. Disclosure of Interest: H. Baraf Grant/Research support from: Takeda, Savient, Regeneron, Nuon, Ardea, Metabolex, Novartis, Consultant for: Regeneron, Savient, Ardea, Speakers Bureau: Takeda, Savient, R. Yood Grant/Research support from: Savient, Takeda, Consultant for: Savient, J. Sundy Grant/Research support from: Ardea Biosciences, Pharmos, Metabolex, Consultant for: Ardea Biosciences, Pharmos, Novartis, F. Ottery Shareholder of: Savient, Employee of: Savient, M. Becker Grant/Research support from: Savient, Takeda, Consultant for: Savient, Takeda, Ardea, BioCryst, Regeneron, URL/Mutual/Metabolex/Chugai